The Influence of Influencer Credibility on Generation Z’S Purchase Decisions Of Azarine Products Through Brand Trust as An Intervening Variable in Bekasi City - Dikson Silitonga (CV. Sakura Digital Nusantara, 2026)
Purpose – This study examines the effect of influencer credibility on Generation Z consumers’ purchase decisions of Azarine skincare products in Bekasi City, with brand trust as a mediating variable. It investigates whether the effect is direct or operates indirectly through brand trust. Design/methodology/approach – A quantitative, descriptive, and causal design was used. The study involved 96 Generation Z consumers in Bekasi City selected through purposive sampling. Data were collected via a five-point Likert questionnaire. Influencer credibility is assessed through three dimensions: trustworthiness, expertise, and attractiveness. Brand trust is evaluated based on reliability, honesty, and safety, while purchase decision is measured through five stages of the decision-making process. Data analysis is conducted using SEM-PLS to examine both direct and indirect relationships among the variables. Finding/Results – Influencer credibility has no significant direct effect on purchase decisions but significantly increases brand trust, which in turn significantly affects purchase decisions. Brand trust fully mediates the relationship, indicating that credibility influences purchasing behavior only through trust formation. Originality/Value – This study highlights brand trust as the key mediating mechanism between influencer credibility and purchase decisions, offering context-specific evidence from Generation Z consumers of Azarine in Bekasi City and enriching research on influencer marketing in the skincare industry